Fundamental of Entrepreneurship ETR300 : Masam Manis Dessert Enterprise / Amira Nur'ain Jasmi... [et al.] - Jasmi, Amira Nur'ain; Hisam, Aina; Bojeng, Afiqah; Zakaria, Ema Fazlina; Mohd Isa, Jannatul Husna (2010)
The name of our restaurant is Masam Manis Enterprise. This business is in form of enterprise which consists of five members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is sells a variety of foods, especially desserts. Our restaurant wants to market "cendol” as the main dessert. This is because "cendol" is one of the signature dishes in East Malaysia. We want to diversify” cendol” become more attractive and popular at Sarawak. Our target customers are the students in the area because of our proximity to UiTM and UNIMAS. Our business operation is at 9 am to 9pm on weekdays except Monday and opens on the weekend. Our restaurant uses the concept of self-service restaurant system and using receipt to purchase food. We have two stalls in the same restaurant. This system is used so that customers can choose a variety of food they want. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Amira Nur’ain bt Jasmi is our General Manager, Ema Fazlina bt Zakaria is the Administration Manager, Aina bt Hisam is the Operation Manager, Jannatul Husna bt Mohd Isa as Financial Manager and Afiqah bt Bojeng as Marketing Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability.